Constructing Ecotourism: The Application of the Tourism System Model in the Philippine Context - Oracion, Enrique G. (Silliman Journal, 2022)
This paper focuses on the concept of ecotourism as a desirable alternative to mass tourism. Using the social constructionist perspective as a theoretical frame, the paper maintains that it is possible to use the tourism system model in the construction of ecotourism as a strategy to promote sustainable resource management and tourism but this approach will only have positive effect if individuals involved in the business of tourism such as brokers, locals, and tourists behave to a tolerable level that will cause the least damage to the local ecosystem. Such behavior, according to the tour-ism system model, could be modified or regulated by the individuals themselves. To exemplify the applicability of the tourism system model as a tool in planning, developing, and managing ecotourism, Apo island in the Philippines is presented as a case study.